DESAIN DAN IMPLEMENTASI SISTEM KELISTRIKAN PADA FASILITAS TERMINAL PELABUHAN PENYEBERANGAN BIAS MUNJUL DI NUSA LEMBONGAN, BALI - Permana Putra, I Made Yogie; Dharma, Agus; Suweden, I Nengah (Jurnal SPEKTRUM, 2024)
Bias Munjul Ferry Port is one of the strategic plans to support tourism in Nusa Lembongan and Nusa Ceningan and support adequate transportation facilities for logistics distribution that must have standards in mechanics and electrical. This study designs electricity for Bias Munjul Ferry Port facilities that are in accordance with standards and compares them with implementation in the field. Data collection was carried out through direct observation and Q&A in the field. The results of the study by designing calculations according to existing standards and provisions for indoor lighting needs, Air Conditioner (AC) needs, grounding, lightning protection, Public Street Lighting (PJU), and hydraulic pump power were then compared with implementation in the field. The results of the implementation of the Bias Munjul Ferry Port facilities showed that there were still some that did not meet the standards after being compared with the results of the design calculations according to existing standards and provisions.